Analysis of the brightness temperature features of the lunar surface using 37 GHz channel data from the Chang'E-2 microwave radiometer. Issue 1 (1st January 2019) - Zhu, Yongchao; Zheng, Yongchun; Fang, Shibo; Zou, Yongliao; Pearson, Simon
Abstract: Compared with other remote observations, brightness temperatures ( T B ) derived from microwave emission measurements provide a unique means to characterize the physical properties of the lunar surface. Using Chang'E-2 microwave radiometer data, we produced 12 global T B images of the lunar surface during a diurnal cycle with different local times separated by approximately 2 h. There are two types of remarkable T B units on the lunar surface, the "hot regions" occurring during the lunar day in the lunar Maria regions and the "microwave cold spots" occurring during the nighttime typically related to young craters. Compared with their surroundings, the hot regions are much warmer during the lunar day and slightly colder at night, while the microwave cold spots are much colder during the lunar night and slightly warmer in the daytime. Moreover, the T B heating and cooling rates of these two units are larger than others at the same average latitude where they are located during the lunar day, especially after sunrise and before sunset. The hot regions have a good agreement with the mare regions with high TiO2 abundance. Besides, brightness temperatures in the lunar Maria correlate closely with their TiO2 abundance. For most microwave cold spots, they agree with the young craters, and their brightness temperature distributions have a significant negative correlation with the lunar surface nighttime temperature and rock abundance.